The Scope of Competence of the Constitutional Court in Deciding Disputes of General Election Results: Ruang Lingkup Kompetensi Mahkamah Konsititusi Memutus Perselisihan Hasil Pemilihan Umum - Firdaus, Firdaus; Kurniawan, Nalom; Lutfi, Muhammad Uut; Jaya, Belardo Prasteya Mega (Jurnal Konstitusi, 2024)
The 1945 Constitution of the Republic of Indonesia (UUD 1945) does not explicitly define “election result disputes.” This definition is only found in several laws and Constitutional Court (MK) Regulations, limited to the context of “vote counting errors.” This research aims to reformulate the concept of election results as an object of dispute in the MK to ensure certainty and justice for candidates and/or candidate pairs. This study uses a normative juridical research method. Elections, as an embodiment of the people’s sovereignty, result in the acquisition of votes and the determination of elected candidates and/or candidate pairs to occupy political positions in government. The resolution of election result disputes in the MK relates to objections to the validity of the vote count, both quantitatively and qualitatively. The examination of the validity of vote acquisition maps the MK’s authority into two scopes: absolute competence and relative competence. The MK’s absolute competence relates to resolving disputes over vote acquisition, while relative competence pertains to ensuring constitutionality, including adherence to election regulations by election organizers during the election stages.